2000
DOI: 10.1159/000007820
|View full text |Cite
|
Sign up to set email alerts
|

<i>Helicobacter pylori</i> Infection: Protection against Barrett’s Mucosa and Neoplasia?

Abstract: Background: Since Helicobacter pylori (Hp) infection provokes intestinal and gastric metaplasia, the question arises whether the specialized metaplasia (Barrett’s mucosa (BM)) and dysplasia or carcinoma in Barrett’s epithelium seen in gastro-oesophageal reflux disease (GORD) might not also be correlated with Hp infection, or whether the latter offers protection against Barrett’s oesophagus and Barrett’s adenocarcinoma. Patients: Gastric and oesophageal biopsies obtained from a total of 2,201 patients were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 36 publications
(43 reference statements)
1
30
0
3
Order By: Relevance
“…H. pylori colonization usually does not cause illness, since 85% of infected people remain asymptomatic throughout life, but infection with strains bearing the cag (cytotoxin-associated gene) pathogenicity island can result in peptic ulcer disease, gastric lymphoma, and gastric adenocarcinoma, the second leading cause of cancer-related deaths, in 15% of infected individuals (2,3). Conversely, there also is increasing evidence of H. pylori providing protection against esophageal and cardial pathologies (4)(5)(6)(7), childhood asthma (8)(9)(10), childhood allergies (9,11), and diabetes and obesity (12). This Gram-negative microaerophilic bacterium of the Epsilonproteobacteria has coevolved with humans for at least 50,000 years, indicating high adaptation capacity to the environmental niche of the human gastric mucosa and suggesting the ability to evade the immune system (13) through mechanisms that are incompletely understood.…”
mentioning
confidence: 99%
“…H. pylori colonization usually does not cause illness, since 85% of infected people remain asymptomatic throughout life, but infection with strains bearing the cag (cytotoxin-associated gene) pathogenicity island can result in peptic ulcer disease, gastric lymphoma, and gastric adenocarcinoma, the second leading cause of cancer-related deaths, in 15% of infected individuals (2,3). Conversely, there also is increasing evidence of H. pylori providing protection against esophageal and cardial pathologies (4)(5)(6)(7), childhood asthma (8)(9)(10), childhood allergies (9,11), and diabetes and obesity (12). This Gram-negative microaerophilic bacterium of the Epsilonproteobacteria has coevolved with humans for at least 50,000 years, indicating high adaptation capacity to the environmental niche of the human gastric mucosa and suggesting the ability to evade the immune system (13) through mechanisms that are incompletely understood.…”
mentioning
confidence: 99%
“…The relationship between H.pylori and BE development seems somewhat complicated. In the literature, there are studies that reach different results on this issue; in addition to the studies reporting that the presence of H.pylori is a risk factor for BE development, there are studies reporting that it does not influence the development of BE or it prevents BE development (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In the study by Vaezi et al (29), it was found that being infected with H.pylori had a protective effect for development of BE and its malignant complications.…”
Section: Does the Presence Of Helicobacter Pylori Affect The Frequencmentioning
confidence: 99%
“…Im deutschen Routineuntersuchungsgut liegt der Anteil der CGastritis mittlerweile bei bis zu 30. Auffällig ist eine Häufung bei Patienten mit gastroösophagealer Refluxkrankheit [2]. Relativ selten ist die Autoimmungastritis, die auf die Magenkorpusschleimhaut beschränkt ist (ca.…”
Section: Epidemiologie Und Wertungunclassified